Respiratory and cardiometabolic comorbidities and stages I to III NSCLC survival: a pooled analysis from the international lung cancer consortium - García Pardo, Miguel; Chang, Amy; Schmid, Sabine; Dong, Mei; Brown, M. Catherine; Christiani, David; Tindel, Hilary Aurora; Brennan, Paul; Chen, Chu; Zhang, Jie; Ryan, Brid M.; Zaridze, David; et al. (Journal of thoracic oncology, 2023)
We explored the association of respiratory and cardiometabolic comorbidities with NSCLC overall survival (OS) and lung cancer-specific survival (LCSS), by stage, in a large, multicontinent NSCLC pooled data set.
Online veröffentlicht am 15. November 2022, Artikelversion vom 24. Februar 2023
Gesehen am 13.12.2023